Outcomes of T-cell lymphoblastic lymphoma in children and adolescents treated with Dana-Farber Cancer Institute Childhood ALL Consortium protocols - Gotti, Giacomo; Flamand, Yael; Koch, Victoria; Testa, Sabrina; Stevenson, Kristen; Tran, Thai-Hoa; Michon, Bruno; Athale, Uma; Silverman, Lewis B.; Pikman, Yana; Place, Andrew E. (Frontiers in Pediatrics, 2026)
Treatment approaches to childhood T-cell lymphoblastic lymphoma (T-LL) are based on those used for T-cell acute lymphoblastic leukemia (T-ALL), but reports of outcomes with contemporary regimens are limited, as patients with LL are often excluded from ALL clinical trials. In this study, we retrospectively analyzed the characteristics and outcome of a cohort of 23 pediatric patients with T-LL treated between 2006 and 2020 according to Dana-Farber Cancer Institute (DFCI) ALL Consortium protocols. Five-year event-free survival, overall survival, and disease-free survival rates were 78.3% (95% CI: 55.4%–90.3%), 87.0% (95% CI: 64.8%–95.6%), and 90% (95% CI: 65.6%–97.4%), respectively. Morphological marrow disease (defined as 5%–24% blasts) at diagnosis was the only feature associated with adverse prognosis. Treatment based on DFCI ALL protocols is an effective strategy for childhood LL and should be considered at the time of treatment selection.